Effect of Antenatal Betamethasone and Dexamethasone on Maternal Blood Glucose Levels, Fetal Movement, Nst Parameters, and Umbilical Artery Doppler - Chaurasia, Amrita; Singh, Vidhi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: The rationale of the study is to establish the time duration of recovery of disturbed sugar values and NST parameters following steroid administration and which drug has a lesser rate of hyperglycemia and lesser disturbance of DFMC and NST parameters, so as to advocate better drugs for fetal lung maturity. This study aims to compare the changes in maternal serum glucose levels, daily fetal movement count, NST parameters, and umbilical artery doppler following Betamethasone and Dexamethasone administration in antenatal women. Subjects and Method: The study design is a prospective observational cohort study. 100 pregnant patients, were recruited into 2 equal groups who received Betamethasone and Dexamethasone in Obstetrics & Gynaecology department, MLN Medical College, Prayagraj. The independent variables are Age, Gravidity, and BMI while the dependent variables are postprandial blood sugar values, Daily Fetal Movement Count, Fetal Heart Rate, Non-Stress Test Parameters, and Doppler Flow Veloci- metry of the Umbilical artery. Categorical variables were compared using the Chi-square test, while, for continuous variables T-test was used. Study instruments include Glucometer, Cardiotocography, and Ultrasound. Results: Significant changes in the glycemic profile and fetal movements were noted. The mean ± SD glucose rise after 24 hrs in Group A (Mean= 140.10; SD= 35.90) and group B (Mean= 113.26; SD= 27.90), with p<0.001. 54% and 24% women perceived reduced fetal movements (p = 0.002) while 14% and 12% women had reduced variability on NST (p = 0.766) in Group A and Group B respectively, with 66.6% and 85.71% showing reduced flow on Doppler. Conclusion: Antenatal Betamethasone as well as Dexamethasone administration causes significant changes in maternal hyperglycemia, FHR, and DFMC at 24hrs while changes were non-significant in NST parameters and Doppler. Maternal hyperglycemia resolved within 72hrs with a resolution of decreased fetal movement perception. Umbilical artery flow decreased 24 hrs following steroid administration with more profound changes with betamethasone.